XBRL: Interactive data visualisation and decision-making process in internet financial reporting - Sharifah Milda Amirul (2022)
Interactive data visualisation (IDV) in the context of internet financial reporting (IFR) has emerged and become more prevalent following the development and implementation of eXtensible Business Reporting Language (XBRL). IDV, which stands for a high-level Website interactivity and features navigation or hyperlinks for IFR representation, may help users process massive amounts of complex information efficiently. Thus, reducing the cognitive load on the users when making financial analyses and judgements. However, the effect of IDV on users' cognition in the context of IFR remained inconclusive because existing research tended to concentrate on the impact of IDV on users' decision-making outcomes rather than the processes involved. It is worth to note that decision-making involves two distinct parts: processes and outcomes. The former can be related to decision accuracy and optimisation. Whereas the latter offers insight into how users interact with information representations like IDV, which can be investigated through user satisfaction and information usability. It is essential to examine users' decision-making processes, as different types of decisions require different information cues that affect their cognition and judgements. Additionally, users' characteristics like their knowledge and experience, and the tasks (simple or complex financial analyses and judgements) influenced the information representation choices they make. Therefore, this study was motivated to investigate the impact of IDV on users' cognitive loads during decision-making processes in the context of IFR. Cognitive Load Theory and Cognitive Fit Theory guided the study's hypotheses, and a 2x2 full factorial experimental design was utilised. The IDV was manipulated into two conditions: high-level interactive websites and low-level interactive websites. Similarly, the financial analyses and judgments, which is known as task characteristics were also manipulated into two conditions: simple or complex tasks. A total of 140 participants participated in this experimental research. The results revealed that users who interacted with the high-level interactive websites reported greater satisfaction than users who interacted with the lowlevel interactive website. Nonetheless, no significant difference was found in the effect of IDV on information usability between users in high-level and low-level interactive webs. Interestingly, it was found that task complexity influenced the relationship between IDV and users' satisfaction. The more complex the task, the higher the user's cognitive load, thus adversely affecting the user's satisfaction. Hence, a greater level of user satisfaction was found only when the users completed simple tasks. Furthermore, the task complexity influenced the relationship between IDV and information usability, where the more complex the task, the higher the user's cognitive load, thus reducing information usability. Excitingly, the study also uncovered that a users' characteristics play a significant role in moderating the effects of task complexity in the relationship between IDV, user satisfaction, and information usability. It revealed that user experience is more profound than user knowledge. User experience significantly affects how complex a task might be perceived in relation to IDV and user satisfaction, as well as affecting IDV and information usability. The effects are stronger when users complete simple tasks in a lowlevel interactive condition. The implications and directions for future research are also discussed.